PEMANFAATAN LIMBAH SEREH WANGI MENJADI INSEKTISIDA BOTANI DI KOTA SOLOK - Eka Candra Lina; Prima Fithri; Valeny Surya Ningsih (Jurnal Hilirisasi IPTEKS, 2021)
The selling price of citronella oil is very low, namely 140,000 Rupiahs/liter and a low yield of 0.5-1.2% of the total refined raw materials are serious problems for citronella farmers in general and the Laiang Jaya farmer group, Solok, West Sumatra. In the distillation process, a large amount of liquid waste (hydrosol) is produced as much as 50%-60%. Hydrosol is an essential oil emulsion that is bound to water and still contains 0.02% essential oil. Insecticidal activity can be increased by adding plant material that has neurotoxic properties such as forest betel (Piper aduncum), which is easily found in forests and vacant lands in the surround of farmers' locations. Isolation of the active ingredients of forest betel is carried out with a distillation system so that it is not difficult for farmers to produce and surely increase their income through alternative use of distilled equipment when it useless. The purpose of this activity is to transfer knowledge related to the utilization of citronella waste into useful products such as raw materials for botanical insecticides. The methods used in this activity are education, workshops, training, mentoring and evaluation of activities. This activity has a positive impact on farmer groups. With this activity, farmer groups understand the importance of technology in product development, produced a prototype in the form of a botanical insecticide from citronella waste. As well as gaining knowledge related to branding and packaging of other citronella oil derivative products that are different from the usual ones.